A study on the turnover intention of teachers in Chinese regional universities: A predictive power analysis based on five management dimensions of high-performance human resource practices. - Jun Li; Lingjie Wang; Xiaoli Xu; Junyan Liu; Lei Peng (PLoS ONE)
In this study, the direct influences of five management dimensions of high-performance human resource practices (HPHRP), i.e., talent selection and cultivation (TSC), career and job security (CJS), performance appraisal and compensation incentives (PACI), participative management (PM), and affective incentives (AI), on Chinese local university teachers' turnover intentions (TI) were investigated. Additionally, the mediating role of organizational commitment (OC) in these relationships was examined. According to the results of a questionnaire survey among 740 teachers from five regional colleges and universities in China, the five management dimensions of HPHRP significantly and negatively impact college teachers' TI, with TSC being the most influential predictor (B = -0.359, t = -10.597***, R² = 0.132), followed by AI ( = -0.277, t = -7.829***, R² = 0.077), PACI ( = -0.262, t = -7.390***, R² = 0.069), CJS ( = -0.262, t = -7.390***, R² = 0.069), and PM ( = -0.231, t = -6.456***, R² = 0.053). Furthermore, OC was found to partially mediate the relationship between TSC (B = -0.243, t = -5.987***, R² = 0.164), CJS (B = -0.105, t = -2.621**, R² = 0.131), PACI (B = -0.127, t = -3.290**, R² = 0.136), and AI (B = -0.126, t = -3.125**, R² = 0.135) on college teachers' TI and completely mediated the influence of PM (B = -0.053, t = -1.288, R² = 0.125) on college teachers' TI. The findings suggest that TSC, OC, and PM play more significant roles in affecting Chinese regional university teachers' TI. In order to reduce teachers' TI, local university administrators should focus on talent, encourage teachers to take part in school management, and strengthen their commitment to the university.